グリーンランド氷床の標高2500m表面における昇華 - 佐藤, 和秀; 平林, 幹啓; 東, 久美子; J.P., Steffensen; Kazuhide, Satow; Motohiro, Hirabayashi; Kumiko, Goto-Azuma (2013)
第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 国立極地研究所 ３階ラウンジ conference object